Continuous Improvement in Learning Innovation Management to Enhance Students’ Learning Motivation - Misbahul Arifin; Jazilurrahman Jazilurrahman; Abdul Haq AS (Business and Applied Management Journal, 2025)
This study examines the role of continuous improvement in managing learning innovation to enhance students’ learning motivation in Islamic junior secondary schools. The research is grounded in the issue that many learning innovations are implemented without sustainable management systems, resulting in inconsistent impacts on student motivation. This study aims to analyse how continuous improvement is implemented in school learning innovation management. A qualitative case study approach was employed, using interviews, observations, and document analysis, with data analysed through an interactive model of reduction, display, and verification. The findings reveal that continuous improvement has been initiated but remains partial, informal, and not yet institutionalised. Learning innovation is practised, but evaluation is largely subjective, data utilisation is limited, and reflective practices are not collaboratively structured. As a result, student motivation increases but fluctuates depending on the quality of implementation. The study concludes that continuous improvement is a key determinant of sustainable innovation and stable student motivation. This research contributes by proposing an integrative model that links continuous improvement, innovation management, and Islamic educational values within a unified framework.